Projected heat-related mortality under climate change in the metropolitan area of Skopje. (December 2016) - Martinez, Gerardo; Baccini, Michela; De Ridder, Koen; Hooyberghs, Hans; Lefebvre, Wouter; Kendrovski, Vladimir; Scott, Kristen; Spasenovska, Margarita
Abstract Background Excessive summer heat is a serious environmental health problem in Skopje, the capital and largest city of the former Yugoslav Republic of Macedonia. This paper attempts to forecast the impact of heat on mortality in Skopje in two future periods under climate change and compare it with a historical baseline period. Methods After ascertaining the relationship between daily mean ambient air temperature and daily mortality in Skopje, we modelled the evolution of ambient temperatures in the city under a Representative Concentration Pathway scenario (RCP8.5) and the evolution of the city population in two future time periods: 2026–2045 and 2081–2100, and in a past time period (1986–2005) to serve as baseline for comparison. We then calculated the projected average annual mortality attributable to heat in the absence of adaptation or acclimatization during those time windows, and evaluated the contribution of each source of uncertainty on the final impact. Results Our estimates suggest that, compared to the baseline period (1986–2005), heat-related mortality in Skopje would more than double in 2026–2045, and more than quadruple in 2081–2100. When considering the impact in 2081–2100, sampling variability around the heat–mortality relationship and climate model explained 40.3 and 46.6 % of total variability. Conclusion These results highlight the importance of a long-term perspective in the public health prevention of heat exposure, particularly in the context of a changing climate.